Gene expression profiling of bone marrow-derived stromal cells seeded onto a sandblasted, large-grit, acid-etched-treated titanium implant surface: The role of the Wnt pathway. (January 2016) - Yang, Guoli; Fang, Wen; Liu, Tie; He, Fuming; Chen, Xuepeng; Zhou, Yi; Guan, Xiaoxu
Highlights: 19 genes were significantly altered after SLA treatment, including LRP5 and Lect2 . Wnt pathway was the most important signals after SLA treatment. LRP5 positively regulated SLA-induced enhanced osteogenic differentiation of BMMSCs. β-Catenin/LRP5 pathway was responsible for this enhanced osteogenic response. Abstract: Objective: The physical and chemical characteristics of the titanium implant surface have been shown to influence dental implant fixation. However, the underlying mechanism by which sandblasted, large-grit, acid-etched (SLA) treatment affects osseointegration remains elusive. Methods: In the present study, the involved target genes and pathways for SLA treatment, which is an extensively used implant surface modification on improving osseointegration, were identified by in vitro microarray and bioinformatics analyses. Results: A total of 19 genes were differentially expressed after SLA treatment, which included Apc2, Fzd1, Frzb, Wnt16, Fzd2, Plau, Wnt5b, Wnt5a, Lrp6, Wnt9a, Sfrp4, Prkch, Calcoco1, Ccnd1, Wif1, Fzd4, Myc, LRP5, and Lect2 . Interaction pathway analyses showed that the Wnt pathway was the most relevant signal after SLA treatment. To ensure the reliability of microarray data, LRP5 was shown to positively regulate osteogenic commitment, extracellular matrix synthesis, and mineralization for BMMSCs seeded onto an SLA-treated titanium surface. However, with LRP5 shRNA treatment, the reduction in calcium deposition in the SLA-treated group was more severe than that observed in cells seeded onto SLA-untreated titanium surface, suggesting that the function of LRP5 was reinforced in the SLA-treated group. In addition, the present study demonstrated that the β-catenin/LRP5 pathway was responsible for the enhanced osteogenic responses of BMMSCs on SLA-treated titanium surface. Conclusions: The findings of the present study serve as an initial step towards understanding the mechanism underlying SLA treatment in osseointegration.